New Quartz Crystal Oscillators Using the Current-Feedback Operational Amplifier - Muhammad Taher Abuelma'atti; Ahmad Al-Ghazwani (Active and Passive Electronic Components)
New crystal oscillators using the current-feedback operational-amplifier (CFOA) are presented. Each circuit uses one CFOA, a crystal and, at most, five externally connected passive elements. Experimental results are included.